2019
DOI: 10.1186/s13046-019-1348-z
|View full text |Cite|
|
Sign up to set email alerts
|

Peglated-H1/pHGFK1 nanoparticles enhance anti-tumor effects of sorafenib by inhibition of drug-induced autophagy and stemness in renal cell carcinoma

Abstract: Background Tumor targeting small molecular inhibitors are the most popular treatments for many malignant diseases, including cancer. However, the lower clinical response and drug resistance still limit their clinical efficacies. HGFK1, the first kringle domain of hepatocyte growth factor, has been defined as a potent anti-angiogenic factor. Here, we aimed to develop and identify novel nanoparticles—PH1/pHGFK1 as potential therapeutic agents for the treatment of renal cell carcinoma (RCC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 50 publications
(66 reference statements)
1
25
0
Order By: Relevance
“…Moreover, the inhibition of autophagy with CQ increased the risk of TEM-induced cell death ( Singla and Bhattacharyya, 2017 ). The Kringle 1 domain of human hepatocyte growth factor (HGFK1) was found to enhance the anti-tumor activities of sorafenib and reverse resistance to this drug in RCC via the inhibition of autophagy ( Gao et al, 2019 ). Recently, a phase I/II trial in patients with RCC showed that the autophagy inhibition achieved by hydroxychloroquine enhanced the anti-tumor effects of mTOR inhibitors ( Haas et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the inhibition of autophagy with CQ increased the risk of TEM-induced cell death ( Singla and Bhattacharyya, 2017 ). The Kringle 1 domain of human hepatocyte growth factor (HGFK1) was found to enhance the anti-tumor activities of sorafenib and reverse resistance to this drug in RCC via the inhibition of autophagy ( Gao et al, 2019 ). Recently, a phase I/II trial in patients with RCC showed that the autophagy inhibition achieved by hydroxychloroquine enhanced the anti-tumor effects of mTOR inhibitors ( Haas et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-30a has been recognized as a potent inhibitor of autophagy by directly targeting Beclin-1 83 . Meanwhile, autophagy activation induced by sorafenib was involved in chemo-resistance in RCC cells 84 . Zheng et al .…”
Section: Regulation Of Autophagy By Mirna In Urologic Cancers (Table 1 )mentioning
confidence: 99%
“…MiR-30a has been recognized as a potent inhibitor of autophagy by directly targeting Beclin-1 [83]. Meanwhile, autophagy activation induced by sorafenib was involved in chemo-resistance in RCC cells [84]. Zheng et al [85] demonstrated that miR-30a overexpression significantly inhibits autophagy activation and enhances sorafenib-induced cytotoxicity in RCC cells.…”
Section: Interaction Of Autophagy and Mirna In Kidney Cancer (Figure 2)mentioning
confidence: 99%
“…Indeed, the Atg4A protein is shown to be responsible for inducing the epithelial-mesenchymal transition as well as stemness properties in various gastric cancer cell lines and in vivo using mice models. As previously mentioned, CSCs are key actors in therapeutic resistance, which is why numerous studies on different types of cancer have proven the beneficial effects of autophagy inhibition on therapy sensitization [50,[65][66][67][68][69][70][71][72]. It has notably been demonstrated in non-small cell lung carcinoma (NSCLC) [67].…”
Section: Rab Family Autophagy and Cscsmentioning
confidence: 99%